Approches de gestion durable et démocratique des forêts dans le monde - Priscilla Gareau (VertigO)
The deforestation, the degradation of forestry ecosystems and the privileged ways to settle the situation, classified under the generic term sustainable management of forests have become important topics on the international political agenda since the last twenty years.  Despite stagnations at the political level, various sustainable and democratic management approaches of forests were experimented through out the world.  This article takes an inventory of political events leading to actual internationals talks over the long-term management of forest and analyses, under an interdisciplinary perspective, the main alternative approaches experimented across the world.  Theses approaches were brought together in three categories:  ecosystemic, integrated and community.